Major Neurological Syndromes with COVID-19: Lessons to Learn - Neeraj Jain; Dnyaneshwar Jadhav; Akash Chheda; Sangeeta Ravat; Rahil Ansari; Mayur Thakkar; Rishikesh Joshi; A. Santosh Sriram; Vrug Durge (Ital Publication, 2022)
Objective: Covid-19 is a highly infectious viral disease, and our understanding of the impact of this virus on the nervous system is limited. Therefore, we aimed to do a systematic analysis of the neurological manifestations. Methods: We retrospectively studied the clinical, laboratory, and radiological findings of patients with major neurological syndromes (MNS) in Covid-19 over 6 months. Results: We had 39 patients with major neurological syndromes (MNS). The most common MNS was cerebrovascular disease (CVD) (61.53%), in which ischemic stroke (83.33%), cortical sinus thrombosis (12.50%), and haemorrhagic stroke (4.16%) were seen. Among ischemic stroke patients, 50% had a large vessel occlusion, and 66.66% of patients with CVD had a significant residual disability. Cranial neuropathy (15.38%), GBS (10.26%), encephalitis (7.26%), and myelitis (5.12%) were the other MNS. Among the three encephalitis cases, two had CSF-Covid-19 PCR positivity and had severe manifestations and a poor outcome. Associated comorbidities included hypertension (30.76%), diabetes mellitus (12.82%), chronic kidney diseases (7.69%), and polycythaemia vera (2.56%). Lung involvement was seen in 64.1% of patients. Mortality was 17.94% in MNS with Covid-19. Conclusions: The most common major neurological syndrome associated with Covid-19 is CVD with increased frequency of large vessel occlusion causing significant morbidity and mortality. Simultaneous lung and other systemic involvement in MNS results in a deleterious outcome.   Doi: 10.28991/SciMedJ-2022-0401-02 Full Text: PDF